2020
DOI: 10.26443/mjm.v9i1.499
|View full text |Cite
|
Sign up to set email alerts
|

A Brave Old World: An Analysis of Scientific Racism and BiDil®

Abstract: N/A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…1). Garrod (2006) explains that “scientists have been satisfied to use false statistics, poor methodology, and illogical conclusions to ‘prove’ the theory that biology is a predictor of culture, without regard for real evidence stating the opposite” (p. 54). Persistent and ingrained belief in biological racial differences in science (Saini, 2019) help sustain scientific racism as a durable feature of modern society.…”
Section: Science and Racementioning
confidence: 99%
See 1 more Smart Citation
“…1). Garrod (2006) explains that “scientists have been satisfied to use false statistics, poor methodology, and illogical conclusions to ‘prove’ the theory that biology is a predictor of culture, without regard for real evidence stating the opposite” (p. 54). Persistent and ingrained belief in biological racial differences in science (Saini, 2019) help sustain scientific racism as a durable feature of modern society.…”
Section: Science and Racementioning
confidence: 99%
“…In providing a historical overview of the application of the concept of race in social practice, Castagna & Sefa Dei (2000) affirmed that sciences, scientific concepts, and scientific theories have long been used to protect, legitimize, and uphold racialized hierarchies. Likewise, Garrod (2006) affirmed, “scientific racism is a scientific tradition in which biology is used not only to prove the existence of race, but also, to maintain existing social hierarchies” (p. 54). This is visible, for example, in The Bell Curve (Herrnstein & Murray, 1994), which presented the argument that race is connected to intelligence, justifying the vast racial inequalities that characterize U.S. society.…”
Section: Science and Racementioning
confidence: 99%
“…Today, the Star Chamber may be gone, but well over 100 Princeton University professors recently petitioned to establish a faculty committee to investigate and discipline other Princeton professors for racism in their research and publications (Smith 2020). 2 These kinds of contemporary concerns over racism in academic research have been raised in virtually every field of inquiry, including the sciences (Garrod 2006).…”
Section: Academic Freedommentioning
confidence: 99%
“…BiDil is a combination of two drugs marketed to Black patients in 2005 to treat heart failure based on the assumption that Black individuals were genetically predisposed to lower nitric oxide bioavailabilitywhich this medication could remedy (Benjamin, 2018;Brody & Hunt, 2006;Garrod, 2006). However, when the trial that suggested this is examined more closely, what emerges is that the patent protection for these two drugs, held by NitroMed, was about to lapse and that combining them for this specific purpose would extend royalties and control for another 13 years.…”
Section: Nutritional Reductionism and Racementioning
confidence: 99%